The absolute mass and index of the heart and lungs in representatives of the marten family (Mustelidae) introduced into zooculture - Orlova Elena; Fedorova Oksana; Paraskiva Ekaterina; Shaposhnikov Georgy (BIO Web of Conferences)
The article presents data on the determination of the mass and heart index of representatives of the marten family (Mustelidae) introduced into zooculture - American mink (Mustela vison Schr., 1777) sable (Martes zibellina L., 1758), and polecat (Mustela putorius L., 1758). Studies have shown that the absolute mass of the heart in the studied fur-bearing animal species depends on body weight. It was revealed that the absolute heart mass of males of all studied marten species is greater than that of females. It was found that the maximum value of the heart index is observed in sable females and males (10,17±0,52 ‰; 10,17±0,68 ‰), minimal in female and male polecats (5,95±1,36 ‰; 4,77±0,22 ‰), female and male American mink occupy an intermediate position in this indicator (6.9 ±0.18 %; 6.7±0.14 %). It was determined that there is no significant difference between animals of different sexes in all studied marten species based on the average heart index. It has been established that the average absolute lung mass of American mink, sable, and polecat does not always depend on their body weight. Sexual dimorphism in absolute lung mass in favor of males was found in minks and polecats, while in sables there is no significant difference between the lung mass of females and males. It was determined that the maximum value of the lung index is observed in females and males of sable (17,8±0,37 ‰; 19,03±0,22 ‰), minimal in female and male American mink (12,2±0,47 ‰; 10,4±0,34 ‰). Female and male polecats occupy an intermediate position according to this feature (16,8±0,8 ‰; 12,1±0,3 ‰). According to the average lung index, female minks and polecats outperform males. In male sables, the lung index exceeds the same index in females.